It takes guts : how your body turns food into fuel (and poop) - Gardy, Jennifer (Greystone Kids, 2021)
"What works all day and night to give you energy and keep you healthy? Your guts, that's what! You probably know that your digestive system (aka your guts) takes everything that you eat and drink, keeps what your body needs, and poops out the rest. But that's not all it does for you! It Takes Guts explores of all the amazing things that happen when we eat and drink: the different tools that the body uses to break food down for digestion, how acids do their part without burning a hole in our stomachs, why we want lots of 'helpful bacteria' in our guts, and how our intestines pass the leftovers along and out the other end. It also explains how the digestive system has a mind of its own, and how it can even affect our moods. And it takes some stomach-turning detours to look at the science of burps, barfs, and farts! Based on the best-selling book Gut: The Inside Story of Our Body's Most Underrated Organ by Giulia Enders (Greystone Books, 2015), It Takes Guts is the perfect illustrated guide for young readers interested in how our bodies work and why what we eat matters."--